Sistem Monitoring Konsumsi Listrik Rumah Tangga dan Perbaikan Faktor Daya dengan Modul GSM Berbasis Mikrokontroller ATmega32 - Abdullah, Abdullah; Risdina, Risdina (LPPM UNIKA Santo Thomas Medan, 2020)
Power factor default is 0.85. if the power factor is less then 085, it will cause a loss to the user. In addition, the low value of the power factor will cause the maximum power capacity not to be used. Therefore designed a monitoring tool and improvement of power factors in household electricity consumption via SMS. This tool is constructed using a combination of current sensor, voltage sensor to determine the work of monitoring system for the use of current, voltage, power, and the value of power factor in householdÂ electricity consumption. In addition, bank capacitors are used to repair on increase the value of power factors and the GSM SIM 800L module is used to sending SMS from the system to the user so that the use of household electricity consumption can be monitored ini real time. Testing is done at home using household loads, namely blender, mixers, CRT TV, refrigerator and washing machines. The test results obtained are the percentage increase in the value of the average power factor of 27.12 % and after an improvement in the power factor usingÂ a capacitor bank can save costs by about 22 % and able to monitor by SMS so this shows that this tool is able to monitor and improve the power factor efficiently